Strengthening health professions regulation in Cambodia: a rapid assessment. Issue 1 (December 2016) - Clarke, David; Duke, Jan; Wuliji, Tana; Smith, Alyson; Phuong, Keat; San, Un
Abstract Background This paper describes a rapid assessment of Cambodia's current system for regulating its health professions. The assessment forms part of a co-design process to set strategic priorities for strengthening health profession regulation to improve the quality and safety of health services. A health system approach for strengthening health professions' regulation is underway and aims to support the Government of Cambodia's plans for scaling up its health workforce, improving health services' safety and quality, and meeting its Association of South East Asian Nations (ASEAN) obligations to facilitate trade in health care services. Methods The assessment used a mixed methods approach including:A desktop review of key laws, plans, reports and other documents relating to the regulation of the health professions in Cambodia (medicine, dentistry, midwifery, nursing and pharmacy); Key informant interviews with stakeholders in Cambodia (The term "stakeholders" refers to government officials, people working on health professional regulation, people working for the various health worker training institutions and health workers at the national and provincial level); Surveys and questionnaires to assess Cambodian stakeholder knowledge of regulation; Self-assessments by members of the five Cambodian regulatory councils regarding key capacities and activities of high-performing regulatory bodies; and A rapid literature review to identify:The key functions of health professional regulation; The key issues affecting the Cambodian health sector (including relevant developments in the wider ASEAN region); and "Smart" health profession regulation practices of possible relevance to Cambodia. Results We found that the current regulatory system only partially meets Cambodia's needs. A number of key regulatory functions are being performed, but overall, the current system was not designed with Cambodia's specific needs in mind. The existing system is also overly complex, with considerable duplication and overlap between governance and regulatory arrangements for the five regulated professions. Conclusions There is considerable scope for reform to the current regulatory system to better align the system to Cambodia's:Current needs and circumstances; Health system strategic priorities; and International obligations. Cambodia is also well placed to base its reformed regulatory system on recent developments of "smart regulatory practices" for health professionals.